Lumicitabine, an orally administered nucleoside analog, in infants hospitalized with respiratory syncytial virus (RSV) infection: Safety, efficacy, and pharmacokinetic results - Oey A. (2023)
Respiratory syncytial virus (RSV) infection is the leading cause of infant hospitalizations and mortality. Lumicitabine, an oral nucleoside analog was studied for the treatment of RSV. The phase 1b and phase 2b studies reported here assessed the safety, pharmacokinetics, and pharmacodynamics of lumicitabine in infants/neonates hospitalized with RSV. In the phase 1b study, infants (≥1 to ≤12 months) and neonates (<28 days) received a single-ascending or multiple-ascending doses (single loading dose [LD] then 9 maintenance doses [MD] of lumicitabine, or placebo [3:1]). In the phase 2b study, infants/children (28 days to ≤36 months old) received lumicitabine 40/20 mg/kg, 60/40 mg/kg LD/MD twice-daily or placebo (1:1:1) for 5 days. Safety, pharmacokinetics, and efficacy parameters were assessed over 28 days. Lumicitabine was associated with a dose-related increase in the incidence and severity of reversible neutropenia. Plasma levels of ALS-008112, the active nucleoside analog, were dose-proportional with comparable mean exposure levels at the highest doses in both studies. There were no significant differences between the lumicitabine groups and placebo in reducing viral load, time to viral non-detectability, and symptom resolution. No emergent resistance-associated substitutions were observed at the RSV L-gene positions of interest. In summary, lumicitabine was associated with a dose-related increase in the incidence and severity of reversible neutropenia and failed to demonstrate antiviral activity in RSV-infected hospitalized infants. This contrasts with the findings of the previous RSV-A adult challenge study where significant antiviral activity was noted, without incidence of neutropenia. Trial registration ClinicalTrials.gov Identifier: NCT02202356 (phase 1b); NCT03333317 (phase 2b).